2010
DOI: 10.1577/c09-050.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Catch, Effort, and Bag Limits on Directed Trips in the Recreational Summer Flounder Party Boat Fishery

Abstract: The summer flounder Paralichthys dentatus is one of the most sought‐after recreational fish along the mid‐Atlantic coast of the United States. This fishery is primarily a consumptive fishery. The stock has been successfully rebuilding but remains below statutory rebuilding goals. Managers accordingly have restrained the annual quota primarily by increasing size limits, with a resulting increase in discard mortality. The purpose of this study was to evaluate new approaches to bag and size limits that minimize d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…A first fish rule would allow vessels to retain all fishes caught until a singleor multiple-species daily bag limit is reached. A cumulative length limit regulation would set a daily length limit such that the sum of the lengths (e.g., TLs) of all retained individuals of a single species could not exceed (Bochenek et al, 2010;.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A first fish rule would allow vessels to retain all fishes caught until a singleor multiple-species daily bag limit is reached. A cumulative length limit regulation would set a daily length limit such that the sum of the lengths (e.g., TLs) of all retained individuals of a single species could not exceed (Bochenek et al, 2010;.…”
Section: Discussionmentioning
confidence: 99%
“…In testing alternative regulations to bag and size limits, Bochenek et al (2010) found that the cumulative length limit scenario decreased discard mortality by up to 63% and increased landings more than 2-fold without increasing fishing mortality rates, compared with levels observed under status quo regulations, in the recreational fishery for summer flounder (Paralichthys dentatus) in New Jersey. However, the efficacy of these types of alternative management strategies for reduction of discards is contingent upon effort reduction and may not be successful if fishermen high-grade live fish or simply target additional species upon reaching the daily bag limit for their primary target species.…”
Section: Discussionmentioning
confidence: 99%
“…1). Detailed descriptions of the party boats, areas fished, and number of trips are provided in Bochenek et al [4].…”
Section: Experimental Designmentioning
confidence: 99%
“…Each angler was given a numbered tag and a one-page flier describing the current day's fishing scenario. One or two observers were present on each trip and collected angler-specific data on kept and discarded summer flounder as the fish were caught [4]. At the end of the trip, observers gave each angler C14 years of age a one-page questionnaire and asked them to complete and return the survey to a marked box prior to leaving the boat.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation